Exploring social-ecological influences on commuter cycling in a midsize northern city: A qualitative study in Thunder Bay, Canada. (April 2021) - Galway, Lindsay P.; Deck, Eve; Carastathis, Joanna; Sanderson, Robert
Abstract: Cycling is a healthy, affordable, and sustainable mode of transportation which offers myriad co-benefits to individuals and society at large. Despite these benefits, cycling remains underutilized as a mode of transportation, particularly in midsize cities and northern climates across North America. The specific objectives of this study were to: (1) explore the lived experiences and social-ecological determinants of utilitarian cycling in the context of a midsize city located in a northern climate, and (2) examine differences in social-ecological influences on utilitarian cycling between cyclists with and without access to a vehicle for transportation. Thirty cyclists over 18 years of age participated in semi-structured interviews. Data collected during the interviews were analysed using thematic analysis to describe the lived experiences of utilitarian cycling and to identify social-ecological determinants of utilitarian cycling. Fourteen key themes emerged from the data, confirming previous research illustrating that utilitarian cycling experiences, practices, and behaviours are determined by a plurality of interacting individual, social and cultural, regulatory and policy, and environmental factors. Across the study sample, differences in the experiences those of cyclists with and without access to a vehicle for transportation were identified across all levels of the social-ecological model. Drawing on our findings, we discuss three key lessons that highlight opportunities for promoting cycling as a mode of transportation in midsize and northern cities in North America in particular. These lessons include: 1) recognizing and addressing the influence of car culture; 2) shifting focus towards utilitarian cycling, and 3) identifying opportunities for addressing winter-related barriers. By drawing on the lived experiences of utilitarian cyclists, this research provides important directives for future policy-making, programming, and infrastructure development for the purposes of promoting cycling as a mode of transportation in other midsize cities in similar environments.